The properties of cement-sand brick containing various percentage of cockle shell as a partial sand replacement - Shahrul Munir, Abdul Nasir (2016)
The increasing demand of cement-sand brick in construction industry nowadays has led to the over-exploitation of natural sand. At the same time, the availability of cockle in this country is relatively high with 43013 metric tonnes of cockle, landed in the year 2014 alone. Furthermore, cockles are often deemed as a form of waste and have no apparent substantial direct use. Nonetheless, cockle shells have been seen as a replacement for natural sand in cement-sand brick production and in turn reduce the abundant of cockle shell waste at disposal area. This thesis presents the mechanical properties of cementsand brick that consist of a variety of cockle shell percentage as a partial sand replacement. The sand was replaced by 0%, 10%, 20%, 30%, 40% and 50% of cockle shell (CS) replacement. The size of the specimens that were used is 210 x100 x 65 (length x width x height). The specimens were then subjected to two types of curing method, namely water and air curing for a period of 7, 28 and 60 days. Subsequently, the specimens were tested for compressive strength, flexural strength and water absorption tests. The compressive strength and flexural strength reached its maximum value at 30% of CS replacement, which suggests that the air curing method delivers the best results for both tests as compared to the water curing method. The strength was also observed to increase as the curing age is increased. As for water absorption test, the results obtained are in accordance to the ASTM CSS-11. Success in combining waste from fisheries industry in the cement sand brick production will able to reduce the use of natural river sand and will decrease the amount of cockle shells disposed at the dumping site.